Digital Dance Criticism: Screens as Choreographic Apparatus - Mattingly, Kate (The International Journal of Screendance, 2019)
Prior to the introduction of websites and social media, professional dance criticism circulated through print publications: newspapers, magazines, and journals. This article examines the current proliferation of screens as platforms for criticism and how they—mobile devices, laptops, televisions, and computers—shift the frameworks that writers and readerships use to engage with dance. I use the concept of a choreographic apparatus to show how digital technologies generate symbiotic relationships between online contexts and contemporary performance. By focusing on three sites—thINKingDANCE, On the Boards TV, and Amara Tabor-Smith’s House/Full of Black Women—I analyze how these platforms challenge widespread assumptions about the disappearance of dance critics.